TLR2-dependent type 1 interferon induction in human monocytes and its relevance to Staphylococcus aureus infection - Musilová, Jana (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2016)
Even though Staphylococcus aureus is a part of healthy microflora, it is also a significant human pathogen causing mild as well as life-threatening infections. Furthermore, an increasing incidence of antibiotic resistant strains within the community comprises a major health risk for patients worldwide. Although there is an extensive research on S. Aureus pathogenicity and immune evasion, our understanding of protective immunity to S. Aureus is limited. So far, attempts for vaccine development against S. aureus were not successful; hence, new insights into the interaction between immune cells and S. aureus are needed. Type I interferons (IFNs) are potent immunomodulators of both innate and adaptive immunity, with a well-defined anti-viral role, yet their role during bacterial infections remains less understood. In addition, studies in mice lacking type I IFN receptor showed contradictory results, especially for S. aureus infections. Toll-like receptor 2 (TLR2) is known to be the key receptor for recognition of Gram-positive bacteria, including S. aureus. S. aureus possesses a wide repertoire of immunostimulatory molecules, such as lipoteichoic acid (LTA), which triggers strong proinflammatory response. However, whether human TLR2 mediates type I IFNs in response to S. aureus remains unclear, as does the impact of type I IFNs on the outcome of S. aureus infection in human cells.
Keywords: Biochemistry and Immunology, Ph.D.; PhD Trinity College Dublin, 2016